2001
DOI: 10.1080/09583150120067553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conventional Pesticides on the Preimaginal Developmental Stages and on Adults of Trichogramma cordubensis (Hymenoptera: Trichogrammatidae)

Abstract: The eVects of seven pesticides sprayed on hosts with parasitoid s at diVerent phases of egg to adult development (24, 24 ± 48, 48± 72, 72 ± 96, 120± 144, 192± 216 h)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 7 publications
4
27
1
4
Order By: Relevance
“…Conversely, Symington (2003) observed that the pupation and adult emergence of the larval endoparasitoid, Orgilus lepidus (Hymenoptera: Braconidae), was hastened (approximately 24h and 48h, respectively) when parasitoids were developing in permethrin-treated host larvae. Vieira et al (2001) did not observe changes in the developmental rate of Trichogramma cordubensis (Hymenoptera: Trichogrammatidae) treated with pyrethroids (deltamethrin and lambda-cyhalothrin) at different preimaginal stages; in this case, the chorion of the host egg most probably provided a protection for the immature stages of the parasitoids, and thus the wasp's preimaginal development was not affected by both pyrethroids.…”
Section: Developmentmentioning
confidence: 90%
“…Conversely, Symington (2003) observed that the pupation and adult emergence of the larval endoparasitoid, Orgilus lepidus (Hymenoptera: Braconidae), was hastened (approximately 24h and 48h, respectively) when parasitoids were developing in permethrin-treated host larvae. Vieira et al (2001) did not observe changes in the developmental rate of Trichogramma cordubensis (Hymenoptera: Trichogrammatidae) treated with pyrethroids (deltamethrin and lambda-cyhalothrin) at different preimaginal stages; in this case, the chorion of the host egg most probably provided a protection for the immature stages of the parasitoids, and thus the wasp's preimaginal development was not affected by both pyrethroids.…”
Section: Developmentmentioning
confidence: 90%
“…This methodology is efficient for toxicological tests for pupae received herbicide all over its surface and avoids death of pupae by asphyxiation (Vieira et al, 2001). After this, pupae were put in contact with P. elaeisis female for 2 d in the glass tube.…”
Section: Herbicides Treatmentmentioning
confidence: 99%
“…Their effectiveness can be significantly lowered by insecticide applications that interfere with parasitism and parasite population growth. Negative effects of insecticides on populations of the parasitoid Trichogramma have been reported [7,8] whereas some studies show that insecticides may increase the performance of natural enemies [9]. Another studies showed that the sublethal effects of insecticides can severely reduce the performance of biological control agents [10].…”
Section: Introductionmentioning
confidence: 99%